Frontiers in Ovarian Cancer Science - Katabuchi, Hidetaka; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This volume presents the latest advances and the current status of our understanding regarding ovarian cancer, addressing both the basic and clinical aspects of the disease. In terms of basic medicine, the WHO Classification of Tumors of Female Reproductive Organs was revised in 2014, and that version addresses several new concepts and histopathological classifications not previously included. One of the most revolutionary breakthroughs concerns the genesis of epithelial ovarian tumors, shifting the focus from the ovarian surface epithelium to serous tubal intraepithelial carcinomas. Clinically, the mortality rate of epithelial ovarian cancer has gradually increased over the past few decades, making it essential to pursue multidisciplinary treatment and apply novel techniques such as neoadjuvant chemotherapy in daily clinical practice. The primary clinical task is the effective treatment of recurrent ovarian cancer with early palliative medicine. Fertility-sparing surgery may also be pursued depending on histologic subtypes, stage, extent of disease, and preexisting ovarian reserve with the concept of oncofertility. On the basis of the considerations described above, each expert author elucidates the science of ovarian cancer in detail, thus providing a collection that will benefit young medical oncologists and seasoned gynecologists and obstetricians alike.
1 Epidemiology and Etiology of Ovarian Cancer -- 2 Hereditary Ovarian Cancer -- 3 Morphologic and Molecular Pathogenesis -- 4 Screening and Prevention of Ovarian Cancer -- 5 Pathology of Epithelial Ovarian Tumors -- 6 Pathology of Non-epithelial Ovarian Tumors -- 7 Ovarian Cancer Genome and Molecular Experimental Sciences -- 8 Strategies for the Management of Epithelial Ovarian Cancer -- 9 Strategies for the Management of Epithelial Ovarian Borderline Tumors -- 10 Strategies for the Management of Non-epithelial $1!# (BOvarian Tumors -- 11 Primary Surgical Treatment of Epithelial Ovarian Cancer -- 12 Primary Chemotherapy and Targeted Molecular Therapy of Epithelial Ovarian Cancer -- 13 Immunotherapy of Epithelial Ovarian Cancer -- 14 Treatment of Recurrent Epithelial Ovarian Cancer -- 15 Management of Adolescent Ovarian Cancer -- 16 Management of Ovarian Cancer in the Elderly Population -- 17 Palliative Medicine in the Management of Ovarian Cancer.s
Keywords: Medicine; Gynecology; Oncology; Reproductive medicine; Medicine & Public Health; Oncology; Gynecology; Reproductive medicine